Acondicionamiento de la superficie de postes de fibra previo a la cementación. - Campaña Mora, Gabriela Lucia (2020)
This research aimed to contrast the different types of conditioning of the fiber post surface prior to cementation based on the action and the advantages and disadvantages that each agent has. Through a bibliographic review and according to the research topic, the sample was determined intentional, non-probabilistic, consisting of 80 articles with a scientific approach, with an ACC greater or equal to 1.50 or in turn with a valid SJR impact factor and whose year of publication ranges between 2010 and 2020. The scientific journals were found from different databases such as Google Scholar, PubMed, Science Direct and Scopus. The collection was carried out with an exhaustive review of each study to be considered. It was a documentary type of investigation, a meta-analysis table was used, which contributed to categorizing the essential information. The results differed, grouping chemical agents that were advantageous for being less abrasive compared to mechanical ones, but both are the most studied, compared and interpreted by the articles used in this work, as well as the implementation of new methods but with little scientific basis such as non-ionizing radiation. It was concluded that there is great discrepancy in determining a conditioning for the improvement of the post-cement interface, for which more in vivo or in vitro studies are proposed that could consider more characteristics of the oral environment. It also considered that there could even be a handling from the manufacturer as a conditioning, due to the sensitivity in handling any technique.